Implementation of Efficient Electric Vehicle Fast Charging System Using Dual Active Bridge Converter - Aung, Myint Myat; Win, Soe; Thar, Hla Aye; Tun, Hla Myo (LPPM Universitas Andalas, 2024)
The paper presents the electric vehicle charging model with fast DC charging technology based on the mathematical modelling and theoretical studies. The problem in this study is to model the fast charging system in order to describe the control and stability of DC bus voltage. The research direction in this study is to design a novel charger in reality. A novel 200 kW fast charger was designed for modeling of fast charging system. The proposed fast charger consists of two portions such as an AC-DC converter and a DC-DC converter using dual active bridge (DAB) technique performing a charging function. The parameters of consumable devices used in the model are mentioned for performance specifications. The main section is a design of transformer that used in the DC-DC converter in order to obtain isolation between the AC system and electric vehicle. This leads to achieve the improvements in the power quality on the AC grid. The performances of the proposed fast charger system were verified through simulations results. The modeling and simulations are performed in MATLAB/SIMULINK and all results confirm the feasibility of proposed design for experimental studies. The recommendation of the system was also given based on the comparison of recent works which were met the objectives of the studies.